Diversity of Plasmids and Genes Encoding Resistance to Extended Spectrum Cephalosporins in Commensal Escherichia coli From Dutch Livestock in 2007–2017 - Ceccarelli, Daniela; Kant, Arie; van Essen-Zandbergen, Alieda; Dierikx, Cindy; Hordijk, Joost; Wit, Ben; Mevius, Dik J.; Veldman, Kees T. (Frontiers in Microbiology, 2019)
Extended-spectrum β-lactamase (ESBL) and plasmid-mediated AmpC β-lactamase (pAmpC) genes confer resistance to extended spectrum cephalosporins and their spread is mostly facilitated by plasmid-mediated horizontal transfer. National surveillance activities to detect ESBL/pAmpC-producers in commensal bacteria from livestock are in place in the Netherlands since several years. This study aimed at reporting gene and plasmid diversity of commensal ESBL/pAmpC-producing Escherichia coli isolated from healthy animals during surveillance activities between 2007 and 2017. A collection of 2304 extended-spectrum cephalosporin-resistant (ESC-R) E. coli isolated from faeces of broilers, dairy cattle, slaughter pigs, turkeys, ducks, and veal calves was investigated and ESBL/pAmpC genes were determined. Gene location of a selection of 473 E. coli isolates was determined and typing of plasmids linked to the ESBL/pAmpC genes was performed. Twenty-two different ESBL/pAmpC genes were identified with blaCTX-M-1 being the most prevalent gene in livestock (43.7%), followed by blaCMY-2 and blaSHV-12, independent of the animal source. Prevalence of typically human associated blaCTX-M-15 was highest in cattle. Less than 10% E. coli isolates owed their ESC-R phenotype to promoter mutations of the chromosomal ampC gene. Majority (92%) of ESBL/pAmpC genes analysed were plasmid located, with IncI1α being the most represented plasmid family in isolates from all animals, followed by IncF (veal calves, dairy cattle and slaughter pigs), IncK (broilers and laying hens), IncX1 in broilers, and emerging IncX3 in broilers and dairy cattle. Prevalence and molecular diversity of ESC-R E. coli isolated from livestock over a 11 year period revealed a composite scenario of gene-plasmid combinations.